Customer Satisfaction Based on Service Quality at the Regional Drinking Water Company (PDAM) Tirta Jaya Mandiri Sukabumi District Palabuhan Ratu Branch - Apriyana, Restu; Andari, Titiek Tjahja; Yulianingsih (MultiTech Publisher, 2024)
The aim of the research is to determine customer satisfaction through service quality at PDAM Tirta Jaya Mandiri, Bogor Regency. The sample in the study amounted to 100. The technique used was purposive sampling, namely a technique for determining samples with certain considerations. Through testing validity, reliability, classical assumptions and linear regression analysis with the help of IBM SPSS. The results obtained show that service quality has a positive and simultaneous effect on customer satisfaction. The test results for the coefficient of determination R (square) were 40%, while the remainder was 34%. The relationship between service quality and consumer satisfaction results in a correlation coefficient of 0.584.